Production and Expression Optimization of Heterologous Serratiopeptidase - Maryam ROUHANI; Vahideh VALIZADEH; Sara MOLASALEHI; Dariush NOROUZIAN (Tehran University of Medical Sciences, 2020)
Background: Serratiopeptidase is a bacterial metalloprotease, which is useful for the treatment of pain and inflammation. It breaks down fibrin, thins the fluids formed during inflammation and acts as an anti-biofilm agent. Because of medicinally important role of the enzyme, we aimed to study the cloning and the expression optimization of serratiopeptidase. Methods: The heat-stable serratiopeptidase (5d7w) was selected as the template. Cloning into pET28a expression vector was performed and confirmed by colony PCR and double restriction enzyme digestion. The recombinant protein was expressed in Esherichia coli BL21 and confirmed by SDS-PAGE and Western blot analysis. Different parameters such as expression vector, culture media, post-induction incubation temperature, inducer concentration, and post-induction incubation time were altered to obtain the highest amount of the recombinant protein. Results: Serratiopeptidase was successfully cloned and expressed under optimized conditions in E. coli which confirmed by western blot analysis. The optimal conditions of expression were determined using pQE30 as vector, cultivating the host bacteria in Terrific Broth (TB) medium, at 37º C, induction by IPTG concentration equal to 0.5 mM, and cells were harvested 4 h after induction. Conclusion: As serratiopeptidase is a multi-potent enzyme, the expressed recombinant protein can be considered as a valuable agent for pharmaceutical applications in further studies.